2016
DOI: 10.1371/journal.pone.0167129
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival Acute Graft-versus-Host Disease in Adult Patients Receiving Allogeneic Hematopoietic Stem Cell Transplantation: A Cohort Study

Abstract: BackgroundTo investigate the incidence, risk factors and survival of conjunctival acute graft-versus-host disease (aGVHD) in adult patients undergoing allogeneic hematopoietic stem cell transplantation (HSCT)MethodsThis retrospective study included a total of 139 patients undergoing allogeneic HSCT between January 2012 and December 2014 at a tertiary referral hospital. Patients with ocular complaints after allogeneic HSCT or first donor lymphocyte infusion were evaluated by ophthalmologists. The risk factors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…oGVHD is a common and potentially severe complication of allogeneic hematopoietic stem cell transplantation (HSCT) [27,28]. Patients who receive allogeneic HSCT develop oGVHD in 40-60% of cases, which significantly impairs their quality of life [29,30]. Using a murine model of hematopoietic stem cell transplantation based on major histocompatibility match and minor histocompatibility mismatch, Heretes et al have demonstrated the infiltration of donor CD4 (and also CD8) T cells in GVHD associated corneal ulcerations [25].…”
Section: Ib T Cell-mediated Inflammation In Ocular Surface Diseasementioning
confidence: 99%
“…oGVHD is a common and potentially severe complication of allogeneic hematopoietic stem cell transplantation (HSCT) [27,28]. Patients who receive allogeneic HSCT develop oGVHD in 40-60% of cases, which significantly impairs their quality of life [29,30]. Using a murine model of hematopoietic stem cell transplantation based on major histocompatibility match and minor histocompatibility mismatch, Heretes et al have demonstrated the infiltration of donor CD4 (and also CD8) T cells in GVHD associated corneal ulcerations [25].…”
Section: Ib T Cell-mediated Inflammation In Ocular Surface Diseasementioning
confidence: 99%
“…A clinical severity score has been proposed for this ocular complication: 0 = absence of ocular surface disease, 1 = presence of conjunctival hyperemia, 2 = presence of conjunctival hyperemia associated with serosanguinous discharge, 3 = presence of pseudomembranous conjunctivitis, 4 = presence of pseudomembranous conjunctivitis associated with corneal epithelial sloughing (Jabs et al, 1989). Recent evidence describes that the severity of ocular surface disorders are correlated with the severity of systemic aGVHD, but it does not affect the patient's survival (Liu et al, 2016).…”
Section: Ocular Manifestationsmentioning
confidence: 99%